2018
DOI: 10.1108/ijph-10-2017-0042
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic characteristics as correlates of psychological distress

Abstract: Purpose The purpose of this paper is to assess the level of psychological distress of offenders newly brought into prison custody in a Nigerian prison and investigate the relationship with socio-demographic and penal characteristics. Design/methodology/approach A cross-sectional study involving 236 new prison entrants who were assessed for psychological distress using the 12-item General Health Questionnaire (GHQ-12) and the Hospital Anxiety and Depression Scale (HADS). Findings A total of 267 prison inmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Attention is paid to the issue of the importance of determining the level of psychological stress of prisoners placed in prisons, thanks to which it is possible to predict what health problems they may have, depending on the conditions prevailing in individual prisons (29). The scale of the problem was confirmed, among others, by studies in Italy, Spain and Nigeria, according to which prisoners, despite health problems, are not properly treated (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Attention is paid to the issue of the importance of determining the level of psychological stress of prisoners placed in prisons, thanks to which it is possible to predict what health problems they may have, depending on the conditions prevailing in individual prisons (29). The scale of the problem was confirmed, among others, by studies in Italy, Spain and Nigeria, according to which prisoners, despite health problems, are not properly treated (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…The root for environmental destructive group events is that it hurts the most fundamental interests of the people, and environmental damage affects people's lives and production safety (Okoro, Ezeonwuka, & Onu, 2018). Figure 1 shows the classification of environmental destructive group events.…”
Section: Characteristics and Causes Of Environmental Destructive Groumentioning
confidence: 99%
“…It was also determined that suicidal thoughts are high (5,21). In a study conducted abroad with 236 newly imprisoned people, anxiety scores were high, with a rate of 66.5%, and depression scores with a rate of 85.2% (22). Similarly, it was shown in another study that prisoners have a risk of suicide rate of 13.2%.…”
Section: Discussionmentioning
confidence: 95%
“…When the literature was reviewed, the number of prison entrances was examined in a limited number of studies, and the psychiatric symptoms of prisoners were questioned (22,25). In a previous study, it was reported that the depression scores of those who had a prison entrance before were higher than those who did not have a prison entrance (22). Another study showed that the idea of suicide was less among prisoners entering prison for the first time (251).…”
Section: Discussionmentioning
confidence: 99%